The effect of air pollution on selected immune system parameters, 8-isoprostane, and alpha-1-antitrypsin of people living in environmentally distinct regions - Vítězslav Jiřík; Ondřej Machaczka; Petra Riedlová; Dagmar Kramná; Grzegorz Siemiatkowski; Leszek Ośródka; Ewa Krajny; Antonín Ambrož; Jan Topinka; Pavel Rössner (Environmental Sciences Europe, 2024)
Abstract Background Air pollution is associated with adverse health effects, especially on the respiratory and cardiovascular systems, but according to recent research, even in cognitive health, metabolic, and immune systems. The objective was to analyse the effect of long-term exposure to air pollution on selected immune system parameters, 8-isoprostane a parameter of oxidative stress, and alpha-1-antitrypsin a protease inhibitor. Methods The number of 381 probands aged 35–65 from two differently polluted regions was included. Lifetime exposures to PM10, PM2.5, NO2, B(a)P, and benzene for each proband were calculated based on historical pollutant concentrations observed. The selected blood parameters were analysed in relation to independent variables (air pollutants, socioeconomic factors, etc.) using multiple regression. Possible covariates were determined. In its end, the study was conceived as a case–control study, and the odds ratio was quantified, expressing the strength of the association of the monitored parameters with the region. Results The average lifetime exposures to air pollution were significantly different between the two regions. Significant effects of the region were observed on IgM, IL-6, 8-isoprostane, and alpha-1-antitrypsin levels. The strongest positive association was observed between 8-isoprostane levels and benzene, PM2.5, PM10 and B(a)P. Odds ratio was 3.21 (95%CI 1.61–6.38). A significant negative association between all pollutants and IgM levels was observed even with covariate adjustment. Odds ratio was 1.80 (95%CI 1.15–2.82). A significant negative association between the alpha-1-antitrypsin levels and PM10, PM2.5, and benzene was found, independent of smoking as a covariate factor. Odds ratio was 1.77 (95%CI 1.09–2.87). In the case of IL-6, a significant effect of especially sleep as a covariate was observed. After covariates adjustment, a significant positive association between the IL-6 levels and PM10 and benzene was only observed. The odds ratio was 1.95 (95%CI 1.28–2.97). Conclusions The study confirmed that long-term exposure to air pollutants is associated with reduced levels of the protease inhibitor alpha-1-antitrypsin and decreased immune system performance by IgM. Furthermore, long-term exposure to air pollutants was associated with increased oxidative stress in humans, measured by 8-isoprostane levels. Residents who live in an industrial, environmentally polluted region showed elevated levels of IL-6.